Gambaran Pola Konsumsi Junk Food dan Kejadian Overweight pada Remaja SMK N 1 Kota Jambi - Haliza, Nur; Indrawati, Iin; Aisah, Aisah; Wulansari, Arnati (Prosiding Seminar Kesehatan Nasional, 2024)
The times and globalization have affected the consumption patterns of adolescents, especially in terms of junk food, which can have an impact on their nutritional status. This study aims to determine the description of junk food consumption patterns and overweight nutritional status in adolescents at SMK N 1 Jambi City. The research method used was descriptive quantitative with a sample of 87 students in grades X and XI, who were selected using proportional sampling technique based on the Lameshow formula. Data collection was done through Food Frequency Questionnaire and anthropometric measurements. Data analysis used univariate analysis method. The results showed that the majority of respondents (56.3%) had “good” junk food consumption patterns, while 43.7% were categorized as “not good”. Nutritional status showed 80.5% of students were not overweight, while 19.5% were overweight. Although most of the respondents had good junk food consumption patterns and normal nutritional status, there was still a proportion of respondents with unfavourable junk food consumption patterns and the prevalence of overweight that needs attention.